Strategi Pemasaran Pada UKM Keripik Tempe Sanan Malang - Rahmi Yuniarti; Arif Rahman; Moch. Choiri (Jurnal Teknik Industri, 2013)
Small and Medium Enterprises (SMEs) have a major role in the economy of country , both in contribution to the Gross Domestic Product and total employment. In order to develop its business, tempeh SME Sanan Chips has to create an innovation and conduct an improvement in order to be able to compete with other businesses. Due to existence of competition among the competitors with different brand of chips, so SME tempeh chips Sanan should improve properly the determination of marketing strategy. Strategy analysis can be conducted by using element of marketing mix. That triggers the necessity to conduct a research in terms of factors appealing marketing and measure how well a united element of marketing mix is performed according to the marketing strategy. After gaining information related to element of marketing mix from the questionnaire given to the SME tempe chips, then analysis is performed based on SWOT and QSMP to determine the major marketing strategy. According to the result, SME Sanan Chips should adopt the marketing strategy by: focusing on product diversity through producing various chips, launching a brand variant with a various pack and net weight in order to offer different choices to the consumers, developing an agent networks to expand the region of market sale, conduct promotion through exhibitions and major events in the Province of East Java, promoting the product intensively through a free advertisement and social media.